Nitrogen-doped TiO2 nanotube array films with enhanced photocatalytic activity under various light sources - Lai, Yue-Kun (2013)
Highly ordered nitrogen-doped titanium dioxide (N-doped TiO2) nanotube array films with enhanced photocatalytic activity were fabricated by electrochemical anodization, followed by a wet immersion and annealing post-treatment. The morphology, structure and compostition of the N-doped TiO2 nanotube array films were investigated by FESEM, XPS, UV-vis and XRD. The effect of annealing temperature on the morphology, structures, photoelectrochemical property and photo-absorption of the N-doped TiO2 nanotube array films was investigated. Liquid chromatography and mass spectrometry were applied to the analysis of the intermediates coming from the photocatalytic degradation of MO. The experimental results showed that there were four primary intermediates existing in the photocatalytic reaction. Compared with the pure TiO2 nanotube array film, the N-doped TiO2 nanotubes exhibited higher photocatalytic activity in degradating methyl orange into non-toxic inorganic products under both UV and simulated sunlight irradiation.